A Phenomenological Study on the Lived Experiences of Secondary Teachers in the Hybrid Classroom During the Covid-19 Crisis - Myrna P. Mandigma (Journal for ReAttach Therapy and Developmental Diversities, 2023)
The study focused on the lived experiences of secondary teachers in a hybrid classroom during the Covid-19 crisis in the state of Arizona and other states in the United States of America where many schools began implementing hybrid classrooms. With schools redesigning instruction during that time, hybrid classrooms with students attending a physical school on certain days and spending a few days remotely for online learning synchronously became the option for continuous learning. Data were collected from 15 participants through one-on-one semi-structured interviews that were done either face-to-face or via Zoom video conferencing. This study was anchored on Husserl’s phenomenological approach. Coding through thematic analysis was employed to generate codes and themes. There were five themes that emerged as a result namely 1) Effective Virtual Learning and Purposive In-Person Classes; 2) Virtual Online Programs Support Hybrid Learning; 3) Challenges in Hybrid Learning Engagement; 4) Needs Assessment is Given Prior to Hybrid Learning; and 5) Open Opportunities to Improve Hybrid Learning. These themes led to the development of a framework at the secondary level of the educational system which apparently emerged from the different categories that were interwoven based on comparative analysis of the data. The emergent framework towards Improved Hybrid Learning may be proposed for schools to further improve their hybrid classroom implementation at the secondary level of education. In general, it may also be beneficial to school administrators, policymakers, educational consultants, teachers, and future researchers even beyond the pandemic, since technology and hybrid learning is here to stay.